THE RELATIONSHIP BETWEEN LIVING CONDITIONS IN THE FAMILY, SUCCESS IN SCHOOL AND INAPPROPRIATE BEHAVIOR IN ADOLESCENTS (Annual of the Faculty of Philosophy in Skopje, 2015)
Insufficient exploration of the relationship of inappropriate behavior among students: family factors, school performance and appearance of some sort of inappropriate behavior, was the main reason to explore this phenomenon. Special emphasis in our research is on the specifics of the appearance in rural areas. The research is aimed at discovering the causes of the family and appearance of inappropriate behavior among adolescents aged 13 to 18 years. Also, the study draws attention to the relationship between the occurrence of inappropriate behavior and poor school performance.The results confirmed the hypothesis according to which there is a connection between family factors, school performance and inappropriate behavior adolescents or adolescents from troubled families, and underachieving students are at higher risk of exhibiting some sort of inappropriate behavior.
Keywords: FAMILY FACTORS; SCHOOL PERFORMANCE; INAPPROPRIATE BEHAVIOR